THE INFLUENCE OF ENTROPY AND DIGITALIZATION ON THE DEVELOPMENT OF ENTERPRISES (Development Service Industry Management, 2024)
The article examines the influence of entropy and digitization on the development of enterprises in the conditions of globalization and localization. Globalization, the integration of global and local markets, is becoming a key factor in the successful development of enterprises, especially in the conditions of growing uncertainty caused by digital transformations. The study emphasizes the importance of glocalization strategies, which allow adapting global approaches to the specifics of local markets, contributing to strengthening the competitiveness of enterprises. The work analyzes the impact of entropic processes on strategic planning, the need to adapt to new conditions and reduce the level of uncertainty due to the introduction of digital technologies. In particular, the role of digitalization in reducing entropy, improving management efficiency, as well as the need to create sustainable business models to ensure the long-term development of enterprises in the digital economy is considered. The authors note that during digitalization, growing entropy increases the level of uncertainty, which forces enterprises to show flexibility and quick adaptation to changes, which emphasizes the need to develop strategies that take into account the impact of digitalization on the structure and dynamics of the market, as well as contribute to the minimization of risks associated with with entropy processes. Market demands require not only adaptation to new technological conditions, but also the creation of sustainable business models capable of functioning effectively in conditions of increased entropy and constant digital transformations. This approach allows enterprises to remain competitive and sustainable in the face of rapid changes and growing market demands.
Keywords: glocalization; digitalization; entropic processes; market integration; strategic planning; competitiveness; local markets; global strategies; digital economy